Metabolic Disorders in Nigerians Occupationally Exposed to Cement Dust - Moses Akiibinu; Mary Adeyemi; Toyosi Ogunbiyi; Mojirade Amusah; Adeolu Amusan; John Anetor (European Scientific Journal, ESJ, 2016)
Exposures to cement dust have been linked with lung dysfunctions in some occupationally exposed workers. There is a dearth of information on the potentials of the cement particles to induce tumorigenesis, kidney failure and oxidative stress in the exposed workers. This study assessed the effects of cement exposure on macrophage activation, tumor markers, kidney injury molecule-1 and markers of oxidative stress in cement loaders with prolonged exposures. Twenty-nine male workers who had direct exposure to cement dust and gases for a period of 2-30 years in Elephant / Lafarge cement depot Ibadan, Nigeria, were recruited for this study. Another twenty apparently healthy individuals who had no interaction with cement served as controls. Levels of carcino-embryonic antigen (CEA), alpha fetoprotein (AFP), kidney injury molecule-1 (KIM-1), DNA-8-hydroxyguanosine (8-OHdG), neopterin, total plasma peroxide (TPP), total antioxidant potential (TAP), oxidative stress index (OSI), malondialdehyde (MDA) and albumin were determined in all participants using ELISA and spectrophotometry methods respectively. The result shows significantly (p0.05) changes observed in the plasma levels of albumin and AFP when compared with the controls. No significant (p>0.05) correlations could be observed between the levels of 8-OHdG, neopterin, albumin, MDA, CEA, AFP, KIM-1 and OSI in the cement exposed workers. Metabolic disorders including excessive macrophage activation, oxidative DNA damage, kidney diseases and chemically-induced tumors are imminent in cement exposed workers.